Validated UV-Vis Spectrophotometric Method for Determination of Gabapentin using Acetyl Acetone and Formaldehyde Reagents: Validated Spectrophotometric Method for Determination of Gabapentin - Nurmaya Effendi; Kosman Rachmat; Passuke Akbar; Naid Tadjuddin (Iranian Journal of Pharmaceutical Sciences, 2013)
Gabapentin is an anticonvulsant widely used in the treatment of epilepsy.An accurate and validated spectrophotometric method was developed as an alternative method to determine gabapentin in pharmaceutical products. This is a simple, accurate, precise, selective and visible spectrophotometric method. The method is based on the measurement of drug absorbance as a result of yellow solution formation reaction between gabapentin and condensation products both from 2 molesacetyl acetone and 1 mole formaldehyde in basic condition (in boric buffer pH 9.5) at 55oC for 15 minutes. The detection was performed at 340 nm.This method is linear in the range of 10.8–80.0 μg/mL with correlation coefficient (r2) of 0.99954. The method was validated according to USP Category I requirements for gabapentin. The validation characteristics include accuracy and precision, linearity, range, limit of detection and limit of quantitation. The acceptance validation criteria were found in all cases.